Anti-racism Training Using the Biopsychosocial Model: Frederick Douglas' Earthquake, Whirlwind, Storm and Fire - Sanders, Mechelle; Fiscella, Kevin (Frontiers in Psychiatry, 2021)
Rochester, New York is home to George Engel and the Biopsychosocial (BPS) model. Rochester was also home to Fredrick Douglas and a stop on the Underground Railroad. More recently, Rochester, New York is also where Daniel Prude died at the hands of the police. In this article, we discuss how our department of family medicine has incorporated race and racism into the BPS model and how we have used it to help primary care trainees become more effective in their work with Black Indigenous and People of Color (BIPOC) patients.